Sources of Knowledge Acquisition in the Education System from the Point of View of Excellent Teachers and Employees in the Field of Knowledge Enhancement in Lorestan Province - Ehsan Geraei; Afsaneh Abdoli; Rezvan Shiri (نشریه مطالعات دانش‌پژوهی)
Purpose: Acquiring knowledge is essential for the educational system to adapt to environmental changes, promote innovative education, and gain a competitive advantage. This study aims to identify the sources of knowledge acquisition in the education system from the viewpoint of distinguished teachers and employees working in the field of knowledge enhancement in Lorestan Province.Methodology: This applied research adopts a qualitative approach. Data were collected through semi-structured interviews and analyzed using qualitative content analysis. The research participants included outstanding teachers, trainers of workshops and courses, and experts organizing training programs for the education sector in Lorestan during the 1402-1403 academic year. A targeted sampling method was employed, and interviews were conducted with 19 experts in the field.Findings: The interview analysis revealed that knowledge acquisition in the education system occurs through four primary sources: media and communication channels, personal knowledge and experiences, educational and research activities, and interpersonal interactions.Conclusion: By identifying the sources of knowledge acquisition within the educational system and enriching these sources, mechanisms can be created to facilitate easier access to them. This will encourage teachers to acquire new knowledge and experiences, which in turn can improve their professional development. Consequently, this process will contribute to the updating of educational methods, enhancing the teaching and learning experience in the classroom, and advancing the educational system at a national level.Value: Understanding the sources of knowledge acquisition for teachers is crucial for the advancement of the teaching profession. It enables teachers to acquire a distinct set of knowledge that can be effectively transferred to students in a comprehensible manner.